Implementation of Virtual and Face-to-Face Childbirth Preparation Training for the Spouses of the Primiparous Women to Reduce the Fear of Childbirth, Improve the Pregnancy Experience, and Enhance Mother- and Father-Infant Attachment: Protocol for a Quasiexperimental Clinical Trial - Zari Doaltabadi; Leila Amiri-Farahani; Seyedeh Batool Hasanpoor-Azghady (Obstetrics and Gynecology International)
Background. Men have a special role to play in promoting maternal and child health during pregnancy, childbirth, and postpartum period. The health of women also requires the participation and cooperation of men. The aim of this study is to compare the effect of virtual and face-to-face childbirth preparation training for spouses of the primiparous women on the pregnancy experience, fear of childbirth (FOC), and mother- and father-infant attachment. Methods. The primiparous women attending the prenatal clinics of Lolagar Hospital and Azadi and Tehransar health centers of Tehran along with their husbands will be studied. The inclusion criteria for the women’s husbands are the first experience of becoming a father, being at least 18 years of age, and the ability to read and write. The exclusion criteria for women’s husbands are the history of physical/mental illness; being a smoker; and consuming alcohol, drugs, or psychotropic substances. The participants will be selected by the convenience sampling method and will be divided into three groups of study A, study B, and control. Spouses in study groups A and B will receive childbirth training through virtual and face-to-face methods with similar content, respectively. The control group only receives ordinary prenatal care. At the 18–20 weeks of gestation, demographic information, pregnancy experience scale (PES), and version A of Wijma delivery expectancy/experience questionnaire (WDEQ-A) will be completed. At 37-38 weeks of gestation, the PES and WDEQ-A questionnaires will be completed again and maternal postnatal attachment scale (MPAS) and postnatal paternal-infant attachment questionnaire (PPAQ) will be completed by the parents 12 weeks after the delivery. Discussion. Improving the experience of pregnancy, especially reducing the FOC and creating a positive attitude towards it, is a vital strategy to promote vaginal childbirth and reduce the number of cesarean sections requested by women. Achieving this will reduce the cost of health care and improve the quality of life during pregnancy, after childbirth, and during the growth and development of infants. Ethics and Dissemination. This research has been funded by the Iran University of Medical Sciences, approved by the Thailand Registry of Clinical Trials, and will commence in May 2020. Results will be disseminated through peer-reviewed journals and shared with the academic and medical community to pregnancy and childbirth outcomes. This trial is registered with TCTR20200515011.